Exploring the Impact of Digital Technology on Oral Traditions: Cultural Preservation in the Digital Era - Nugroho, Wawan Setiaji; Kesyafano, Benni (IHSA Institute, 2025)
The preservation of oral traditions in the digital era presents a complex and multifaceted challenge that intersects tradition with technology. This research delves into the dynamic interplay between oral cultures and the digital landscape, exploring how digital technologies shape the preservation, transmission, and evolution of oral traditions while also examining the broader cultural implications of this intersection. Drawing upon insights from cultural anthropology, folklore studies, communication theories, and digital humanities, the research uncovers key findings that deepen our understanding of the opportunities and challenges posed by digital technologies. While digital platforms offer unprecedented opportunities for the documentation, dissemination, and revitalization of oral cultures, they also present challenges to their authenticity, integrity, and sustainability. The research offers recommendations for policymakers, cultural organizations, and community leaders to support the sustainable preservation of oral traditions in the digital era, emphasizing the importance of collaboration, innovation, and cultural sensitivity in navigating this evolving landscape.